Analysis of Rainfall in Pine Forest in Taman Hutan Raya Bukit Barisan Tongkoh Kabupaten Karo Based on Water Balance Model - Riauli Anggriani Pardede; Sumono .; Nazif Ichwan; Edi Susanto (Universitas Sumatera Utara, 2013)
Water balance model is stacked to predict soil moisture storage in pine forest. The balance is the appropriate between the coming rainfall and the going water from pine forest. Water balance model consists of rainfall, throughfall, stemflow, interception, actual evapotranspiration, and run off. The results of research showed that daily rainfall was 16,326 mm/day and annual rainfall was 2309 mm/year. Actual evapotranspiration was 2,546 mm/day. Soil moisture storage found during 4 months the research was 385,450 mm, therefore it can be concluded that the research region was suitable for growing of pine forest.